Efficacy and Safety of Elvitegravir/Cobicistat/Emtricitabine/Tenofovir Disoproxil Fumarate in Asian Subjects with Human Immunodeficiency Virus 1 Infection: A Sub-Analysis of Phase 3 Clinical Trials - Choi, Jun Yong; Sungkanuparph, Somnuek; Anekthananon, Thanomsak; Sax, Paul; DeJesus, Edwin; Edelstein, Howard; Nelson, Mark; DeMorin, Jennifer; Liu, Hui C.; Swamy, Raji; Bahn, Joonwoo; Hwang, SunJin; et al. (Infection & chemotherapy, 2016)
The efficacy and safety of a single tablet regimen (STR) of elvitegravir/cobicistat/emtricitabine/tenofovir disoproxil fumarate (E/C/F/TDF) were analyzed in Phase 3 clinical trials in antiretroviral therapy (ART)-naïve and ART-experienced Asian subjects infected with human immunodeficiency virus (HIV)-1. Studies GS-US-236-102 and GS-US-236-103 were randomized, double-blind, placebo-controlled, 144-week studies conducted in ART-naïve subjects, comparing E/C/F/TDF versus efavirenz (EFV)/F/TDF or ritonavir-boosted atazanavir (ATV+RTV) plus emtricitabine/tenofovir DF (F/TDF), respectively. Studies GS-US-236-115 and GS-US-236-121 were randomized, open-label, 96-week long conducted in ART-experienced subjects, who switched to E/C/F/TDF from ritonavir-boosted protease inhibitors (PI+RTV)+F/TDF, or non-nucleoside reverse transcriptase inhibitors (NNRTI)+F/TDF regimens. The E/C/F/TDF appeared to have sustained efficacy and safety and was well tolerated in the small number of ART-naïve and ART-experienced Asian subjects.